The War of Yemen and The International Court Decision: A Houthi Case Fighting (Universitas Negeri Semarang, 2021)
In the existence of international relations, of course there are not only positive things but also negative things, one of which is that it can cause a conflict within or that can be called an international dispute. An international dispute is a dispute between subjects of international law that can be about facts, law or politics in which a claim or inclusion of one party is rejected, claimed back or denied by another party. International disputes themselves are also based on type and type. Based on the type there are political disputes and also legal disputes. International disputes can also occur due to many factors such as terrorism, the ruling regime in a country, culture, territorial territoriality, a country's intervention on the sovereignty of another country, natural resources, foreign policy that is too flexible or otherwise too rigid, moral elements , itas and politeness of the nation, the problem of claims of national or territorial power boundaries, economic problems and many more which are of course related to subjects in international law. Yemen is a country that is currently experiencing an international dispute. The Yemeni War is a war that is a continuing war. This war began in 2015 or four years ago. In the Yemen war it was also called a civil war involving two parties namely Abdrabuh Mansur Hadi who led the Yemeni government (officially recognized by the International) with an armed movement called the Houthis and their supporters. So these two camps both claim that they are the official government of Yemen. The war is ongoing. The Ansar Allah group, which is often referred to as Ansarullahh or Houthi, is a Zaidi group originating from the Governor of Sa'dah in the mountains on the northern border of Yemen with Saudi Arabia. This conflict continued to occur continuously during the 2000s which sometimes experienced an increase and shrinkage. Some steps have also been taken to resolve this conflict but during the negotiations failed.